The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1038/nature05519
|View full text |Cite
|
Sign up to set email alerts
|

Repression of the human dihydrofolate reductase gene by a non-coding interfering transcript

Abstract: Alternative promoters within the same gene are a general phenomenon in gene expression. Mechanisms of their selective regulation vary from one gene to another and are still poorly understood. Here we show that in quiescent cells the mechanism of transcriptional repression of the major promoter of the gene encoding dihydrofolate reductase depends on a non-coding transcript initiated from the upstream minor promoter and involves both the direct interaction of the RNA and promoter-specific interference. The speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
481
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 655 publications
(493 citation statements)
references
References 21 publications
8
481
0
Order By: Relevance
“…Martens et al 28) found that lncRNA-SRG1 transcript across the SER3 promoter interferes with the binding of activators, thus regulating SER3 repression. Martianov et al 29) demonstrated that noncoding RNA could directly interact with the general transcription factor IIB and format a stable complex, which could dissociate the preinitiation complex and major promoter, thus decreasing dihydrofolate reductase gene expression. Wang et al 30) found that ncRNACCND1 could recruit an RNA-binding protein chain); (c) Intronic: stemming from the introns of the protein-coding genes; (d) Intergenic: located between two protein-coding genes [termed long intergenic noncoding RNAs (lincRNAs)]; and (e) Bidirectional: produced by the upstream sequence and the opposite direction of protein-coding genes 3,14) .…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…Martens et al 28) found that lncRNA-SRG1 transcript across the SER3 promoter interferes with the binding of activators, thus regulating SER3 repression. Martianov et al 29) demonstrated that noncoding RNA could directly interact with the general transcription factor IIB and format a stable complex, which could dissociate the preinitiation complex and major promoter, thus decreasing dihydrofolate reductase gene expression. Wang et al 30) found that ncRNACCND1 could recruit an RNA-binding protein chain); (c) Intronic: stemming from the introns of the protein-coding genes; (d) Intergenic: located between two protein-coding genes [termed long intergenic noncoding RNAs (lincRNAs)]; and (e) Bidirectional: produced by the upstream sequence and the opposite direction of protein-coding genes 3,14) .…”
Section: Transcriptional Regulationmentioning
confidence: 99%
“…First, it is currently unknown how many lncRNAs utilize R-loops as a mechanism for gene regulation. It has been speculated for some time that direct hybridization of lncRNAs with genomic DNA could be a mechanism for locus-specific targeting, however, with the exception of RNA:DNA:DNA triplexes, [85][86][87] this has yet to be broadly demonstrated. Another question is how an RNA invades a DNA duplex, an activity that is thermodynamically unfavorable.…”
mentioning
confidence: 99%
“…Another example is the 3′ end of yeast lncRNA Srg1, which overlaps the promoter of the target gene Ser3 and inhibits Ser3 expression by occupying the binding site for transcription initiation factors in the Ser3 promoter [44]. At the transcriptional level, some lncRNAs inhibit the transcription of target genes by binding to the promoters of target genes and forming stable DNA-RNA triplex complexes [45], while others cooperate with transcription modulators in transcriptional regulation and interfere with the formation of the transcription initiation complex to repress transcription initiation and to rapidly alter gene expression patterns [46]. Post-transcriptionally, the formation of a RNA dimer via complementary base pairing between the lncRNA and the target mRNA can block the binding sites of transcription factors and processing-related factors, which regulate mRNA splicing, translation and degradation [47].…”
mentioning
confidence: 99%